Urban Trauma and Self-organization of the City. Autopoiesis in the Battle of Mogadishu and the Siege of Sarajevo - Aquilué, Ines; Lekovic, Milica; Ruiz Sánchez, Javier (Urban, 2016)
Introduction Cities under armed conflict become urban laboratories. Changes of their urban structure reflect intrinsic properties of the city, hardly noticeable in circumstances of stability. Not only does a conflict-conditioned urban trauma imply shattered spatial and social networks, it also removes memory from space, jeopardizing both city´s history and future. However, viewed through the lens of complexity, “trauma is an element that is not external, but intrinsically constitutive of a city´s organization” (Burke, 2010) – it defines the moment in which the urban system needs to reinvent itself in order not to disappear. In that sense, our object of study addresses an urban specificity that usually occurs in urban conflicts of high uncertainty: self-organization. This paper briefly exposes two cases that concern self-referential systems in war situations. The first case is the city of Mogadishu (Somalia) during the October 1993 pacification attempt by the U.S. Special Forces and the second is the city of Sarajevo (Bosnia and Herzegovina), held under siege for more than three and a half years, between April 1992 and December 1995, by Bosnian Serb troops. In both cases, armed conflict caused an increase of self-organization in the urban system, changing its future unpredictably and irreversibly. Keywords Battle of Mogadishu; Siege of Sarajevo; complex urban systems; autopoiesis; urban armed conflict